2012
DOI: 10.1088/0031-9155/57/22/7329
|View full text |Cite
|
Sign up to set email alerts
|

Methods for robustin vivostrain estimation in the carotid artery

Abstract: A hierarchical block-matching motion tracking algorithm for strain imaging is presented. Displacements are estimated with improved robustness and precision by utilizing a Bayesian regularization algorithm and an unbiased subsample interpolation technique. A modified least-squares strain estimator is proposed to estimate strain images from a noisy displacement input while addressing the motion discontinuity at the wall-lumen boundary. Methods to track deformation over the cardiac cycle incorporate a dynamic fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 85 publications
0
73
0
2
Order By: Relevance
“…Although a by-product of the time series analysis process, the mechanical strain is also useful to identify soft lipid pools. Due to the stiffness contrast with its surroundings, soft lipid pools can be identified with a high magnitude of mechanical strain – a fact that is used in ultrasound elasticity imaging (UEI) [32]–[34]. …”
Section: Results and Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a by-product of the time series analysis process, the mechanical strain is also useful to identify soft lipid pools. Due to the stiffness contrast with its surroundings, soft lipid pools can be identified with a high magnitude of mechanical strain – a fact that is used in ultrasound elasticity imaging (UEI) [32]–[34]. …”
Section: Results and Observationsmentioning
confidence: 99%
“…Although noninvasive UEI can also detect large soft lipid pools in plaques [32]–[34], the results are sometimes difficult to interpret due to complex mechanical boundary conditions. US-TSI can provide complementary information to UEI, and the thermal strain image and elasticity image co-registered with US B-mode image can provide comprehensive information to assess the vulnerability of a plaque.…”
Section: Discussionmentioning
confidence: 99%
“…Many arterial strain imaging techniques have already been developed and reported, like intravascular techniques [9], which use an US transducer on the tip of a catheter to image from within the lumen, and non-invasive techniques, which image from outside the body [10][11][12][13][14][15]. With these techniques, it has been shown that arterial strain distribution correlates with histological composition of plaques in pigs [16] and in humans [2,17].…”
Section: Introductionmentioning
confidence: 99%
“…The role of kinematic features, which are estimated with motion analysis from B-mode US image sequences and represent dynamic phenomena and mechanical interactions occurring during the cardiac cycle (CC), remains unexplored, though. None of the related studies has considered kinematic features in CAD systems for CA, while only a few research groups have investigated potential motion-based risk markers [20], [21].…”
Section: Introductionmentioning
confidence: 99%